Free Radical Formation in Novel Carotenoid Metal Ion Complexes of Astaxanthin - Polyakov, Nikolay E. (2010)
The carotenoid astaxanthin forms novel metal ion complexes with Ca(2+), Zn(2+) and Fe(2+). MS and NMR measurements indicate that the two oxygen atoms on the terminal cyclohexene ring of astaxanthin chelate the metal to form 1:1 complexes with Ca(2+) and Zn(2+) at low salt concentrations < 0.2 mM. The stability constants of these complexes increased by a factor of 85 upon changing the solvent from acetonitrile to ethanol for Ca(2+) and by a factor of 7 for Zn(2+) as a consequence of acetonitrile being a part of the complex. Optical studies showed that at high concentrations (> 0.2 mM) of salt 2:1 metal:astaxanthin complexes were formed in ethanol. In the presence of Ca(2+) and Zn(2+) salts the lifetime of the radical cation and dication formed electrochemically decreased relative to that of the carotenoid neutral radical. DFT calculations showed that the deprotonation of the radical cation at the carbon C3 position resulted in the lowest energy neutral radical while proton loss at the C5, C9 or C13 methyl groups was less favorable. Pulsed EPR measurements were carried out on UV-produced radicals of astaxanthin supported on silica-alumina, MCM-41 or Ti-MCM-41. The pulsed EPR measurements detected the radical cation and neutral radicals formed by proton loss at 77 K from the C3, C5, C9, and C13-methyl groups and a radical anion formed by deprotonation of the neutral radical at C3. There was more than an order of magnitude increase in the concentration of radicals on Ti-MCM-41 relative to MCM-41, and the radical cation concentration exceeded that of the neutral radicals.